ANALISIS KETERLAKSANAAN PEMBELAJARAN BERBASIS ANDROID KONSEP IPA DI SD PADA CALON GURU SEKOLAH DASAR - Heny Sulistyaningrum; Sri Cacik; Anggun Winata (Universitas Muhammadiyah Gresik, 2020)
Current learning development. involves a process of learning that makes learners ready to compete in the global world through a skill called 21st century skills and students are no exception. The use of technology in learning is very important in facilitating students in quality learning such as the use of smartphones with Android applications in learning. The study aims to determine the feasibility of implementing android-based learning science concepts in elementary schools in elementary school teacher candidates. This research is a qualitative descriptive study to describe the results of an analysis of the implementation of android-based learning of science concepts in elementary schools to prospective elementary school teachers. The research subjects were 10 students who were conducted at the 2018 Class A PGSD UNIROW students using the observation sheet of Android-based learning implementation and supported by student and teacher interview sheets. Based on the results of the implementation of the learning of science concepts in elementary school, it can be seen that all aspects including aspects of the evaluation of syntax, social systems, and the principles of reaction and management have very good results, which are more than 85%. These results indicate that the development of an Android-based learning device that has been carried out is in accordance with the plan created with its implementation in the field.